The Relevance of Mosque Financial Inclusion and Economic Sustainability - Holle, Mohammad H; Asiyah, Binti Nur; Zumaroh, Zumaroh; Koerniawati, Dwi; Mohamad, Syed Ismail Syed; Pellu, Arifin (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study aims to investigate the relevance of mosque-based financial inclusion in promoting sustainable economic development, using case studies from Jogokariyan Mosque in Yogyakarta and Sabilillah Mosque in Malang, Indonesia. Employing a qualitative, policy-oriented case study approach, the research explores how Islamic social finance instruments—particularly zakāh, infāq, and ṣadaqah (ZIS)—are leveraged through mosque-based institutions to deliver accessible, interest-free, and community-centered financial services outside the formal banking sector. The findings demonstrate that mosques can function as effective platforms for grassroots financial inclusion, offering consumptive and productive support via mechanisms such as qarḍ ḥasan, microgrants, and cooperative savings. These practices contribute not only to financial access but also to enhanced social capital and community trust. Theoretically, this research advances the discourse on Islamic economic empowerment by framing mosques as decentralized agents of inclusive financial ecosystems. It introduces a practical model for sustainable Islamic microfinance, grounded in Shariah principles and responsive to socio-economic inequality. This study invites future cross-regional and cross-faith research into mosque-led financial inclusion as an alternative strategy for inclusive growth, especially in underserved or unbanked populations globally.